Application of passive sampling for sensitive time-integrative monitoring of cyanobacterial toxins microcystins in drinking water treatment plants - Jaša, Libor; Sadílek, Jan; Kohoutek, Jiří; Straková, Lucie; Maršálek, Blahoslav; Babica, Pavel (Water research, 2019)
Calibrated adsorption-based passive samplers were used for time-integrative monitoring of microcystins (MCs) in three full-scale drinking water treatment plants (DWTPs) in the Czech Republic during two vegetation seasons (Jun-Nov), in parallel with traditional discrete sampling. MCs were detected in epilimnetic water samples at concentrations up to 14 μg/L, but their levels in raw water in DWTPs were below 1 μg/L WHO guideline value for drinking water. Conventional treatment technologies (coagulation/filtration) eliminated cyanobacteria and intracellular toxins but had a limited removal efficiency for extracellular toxins. MCs were regularly detected in final treated water, especially in DWTPs equipped only with the conventional treatment, but their concentrations were below the quantitation limit of discrete sampling (<25 ng/L). Passive samplers in combination with LC-MS/MS analysis provided excellent sensitivity allowing to detect time-weighted average (TWA) concentrations of MCs as low as 20-200 pg/L after 14-d deployment. Median MC TWA concentrations in the treated water from the individual DWTPs were 1-12 ng/L, and most likely did not present significant health risks. Passive samplers well reflected spatiotemporal variations of MCs, actual concentrations of extracellular toxins, MC removal efficiency in DWTPs, and toxin concentrations in the treated water. Passive sampling can be effectively used for assessment and management of MC health risks during DWTP operation.
Keywords: Environmental Monitoring; čištění vody; Marine Toxins; tandemová hmotnostní spektrometrie; pitná voda; monitorování životního prostředí; mikrocystiny; Chromatography, Liquid; Water Purification; bakteriální toxiny; chromatografie kapalinová; Česká republika; Microcystins; Tandem Mass Spectrometry; Drinking Water; Bacterial Toxins; mořské toxiny; Czech Republic